The kinematics of table tennis racquet: differences between topspin strokes - Bańkosz, Ziemowit; Winiarski, Sławomir (The Journal of sports medicine and physical fitness, 2017)
Studies of shot kinematics in table tennis have not been sufficiently described in the literature. The assessment of the racquet trajectory, its speed and time characteristics makes it possible to emphasize on certain technical elements in the training process in order, for example, to increase strength, speed of rotation or speed of the shot while maintaining its accuracy. The aim of this work was to measure selected kinematic parameters of table tennis racquet during forehand and backhand topspin shots, while considering the differences between these strokes in table tennis. The measurements took place in a certified biomechanical laboratory using a motion analysis system. The study involved 12 female table tennis players in high-level sports training and performance. Each subject had to complete series of six tasks, presenting different varieties of topspin shots. The longest racquet trajectory was related to forehand shots, shots played against a ball with backspin and winner shots. The maximum racquet velocity was precisely in the moment of impact with the ball. The individual of velocity and distance were larger in the direction of the acting force, depending on the individual shot. Changing the type of topspin shot requires changes of time, velocity and primarily distance parameters as well as the direction of the playing racquet. The maximum speed of the racquet occurring at the moment of the impact is probably the most important principle in playing technique. The results can be directly used in improving training of table tennis techniques, especially in the application and use of topspin shots.